Modern neurobiological theories of consciousness as a basis for the prevention and treatment of burnout: innovations, experience, and perspectives - Rusanov, Volodymyr (Psychosomatic Medicine and General Practice, 2025)
Introduction. Burnout syndrome (BS) is one of the most pressing challenges in modern medicine, especially in the context of the war in Ukraine, where the burden on the healthcare system has significantly increased. This condition not only deteriorates mental and physical health, reducing the quality of life for both patients and medical professionals, but also induces additional stress in professional environments. Burnout increases the risk of medical errors, reduces the efficiency of multidisciplinary teams, and threatens the stability of the healthcare system. Furthermore, this phenomenon significantly impacts the country’s economy, complicating the recovery of economic and social infrastructure. Neurobiological theories of consciousness, such as the Neural Correlates of Consciousness (NCC), the Global Workspace Theory (GWT), and the Integrated Information Theory (IIT), offer new perspectives for understanding the neural mechanisms underlying burnout. These theories allow for the study of neural network dynamics, emotional regulation, and the brain’s adaptive mechanisms, which are crucial for preventing and treating this condition. Objective of the Study. To assess the potential application of knowledge from neurobiological theories of consciousness in developing effective strategies for preventing and treating burnout, with a particular focus on its use in the practice of psychotherapists, psychiatrists, and medical psychologists. Materials and Methods. This analysis includes results from modern scientific studies in the field of neurobiology of consciousness, published in peer-reviewed journals over the past 20 years. Particular attention was given to publications examining the connection between neurobiological theories of consciousness, burnout syndrome, and the effectiveness of therapeutic approaches. Results. The study demonstrated that burnout is associated with dysfunctions in the brain’s global workspace, reduced information integration in the cortex, and impairments in neural correlates of consciousness. Recent research has found that the use of neuroimaging methods facilitates the early detection of changes in neural networks associated with burnout. Furthermore, the implementation of strategies based on neuroplasticity, mindfulness, cognitive-behavioral therapy (CBT), and adaptive stress management approaches has shown high effectiveness in preventing and treating this condition. Conclusions. Integrating neurobiological theories of consciousness into clinical practice can significantly enhance the effectiveness of burnout therapy. Particularly promising approaches include neuroplasticity-based interventions, cognitive process regulation through the global workspace, and innovative neuromodulation technologies. These advancements lay the foundation for new standards in psychotherapeutic practice, aimed at improving the quality of life for both patients and professionals. In practical terms, this necessitates the implementation of modern neuroimaging methods for diagnosis, personalized therapeutic approaches, psychotherapy oriented toward neuroplasticity, and strategies for emotional regulation training and stress management.